Supramolecular synthon hierarchy in bumetanide cocrystals - Allu, Suryanarayana; Bolla, Geetha; Tothadi, Srinu; Nangia, Ashwini (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Novel cocrystals of sulfonamide drug Bumetanide with carboxamides are developed based on supramolecular synthons approach

Supramolecular synthons in bumetanide cocrystals and ternary products - Allu, Suryanarayana; Bolla, Geetha; Tothadi, Srinu; Nangia, Ashwini (Crystal Growth & Design, 2017)
A novel design strategy for cocrystals of the diuretic sulfonamide drug bumetanide (BUM) with carboxamides is reported based on reliable supramolecular synthons. Binary cocrystals of BUM with pyridine carboxamides, pyridones, and cytosine were obtained by solvent assisted grinding followed by solution crystallization. All cocrystal structures exhibit hydrogen bonding of the coformer with the carboxylic acid group of BUM via heterosynthons which replace the acid homodimer in the drug crystal structure. Pyridones are inserted as N-H center dot center dot center dot O dimers which are in turn bonded to the acid group of BUM, while the pyridine amide coformers interact via the acid amide heterosynthon. Cocrystal polymorphs were obtained for bumetanide isonicotinamide cocrystal structure with the sulfonamide pyridine and sulfonamide acid synthons. Careful crystal packing analysis of BUM structure and nine new binary adducts gave an idea for the design ternary cocrystals, and subsequently four new ternary crystalline products were crystallized. Whereas the binary cocrystal structures were confirmed by single crystal diffraction, the ternary combinations were chatacterized by their unique powder X-ray diffraction patterns as well as by thermal and spectroscopic techniques.

Systematic synthesis of a 6-component organic-salt alloy of naftopidil, and pentanary, quaternary and ternary multicomponent crystals - Dandela, Rambabu; Tothadi, Srinu; Marelli, Udaya Kiran; Nangia, Ashwini (IUCrJ, 2018)
The single-crystal X-ray structure of a 6-component organic-salt alloy (hexanary) of naftopidil (1) (an active pharmaceutical ingredient) with benzoic acid (2) and four different hydroxy-substituted benzoic acids, i.e. salicylic acid (3), 2,3-dihydroxybenzoic acid (4), 2,4-dihydroxybenzoic acid (5) and 2,6-dihydroxybenzoic acid (6), is reported. The hexanary assembly originates from the observation that the binary salts of naftopidil with the above acids are isostructural. In addition to the 6-component solid, we also describe five 5-component, ten 4-component, and ten 3-component organic-salt alloys of naftopidil (1) with carboxylic acids (2)-(6). These alloys were obtained from different combinations of the acids with the drug. The synthetic design of the multicomponent organic alloys is based on the rationale of geometrical factors (shape and size) and chemical interactions (hydrogen bonds). The common supramolecular synthon in all these crystal structures was the cyclic N+ - H center dot center dot center dot O- and O-H center dot center dot center dot O hydrogen-bonded motif of R-2(2) (9) graph set between the 2-hydroxyammonium group of naftopidil and the carboxylate anion. This ionic synthon is strong and robust, directing the isostructural assembly of naftopidil with up to five different carboxylic acids in the crystal structure together with the lower-level multicomponent adducts. Solution crystallization by slow evaporation provided the multicomponent organic salts and alloys which were characterized by a combination of single-crystal X-ray diffraction, powder X-ray diffraction, NMR and differential scanning calorimetry techniques.

Saturated N-heterocyclic carbene based thiele's hydrocarbon with a tetrafluorophenylene linker - Kundu, Gargi; De, Sriman; Tothadi, Srinu; Das, Abhishek; Koley, Debasis; Sen, Sakya S. (Chemistry-A European Journal, 2019)
The synthesis of a SIPr [1,3-bis(2,6-diisopropylphenyl)-imidazolin-2-ylidene] derived Kekule diradicaloid with a tetrafluorophenylene spacer (3) has been described. Two synthetic routes have been reported to access 3. The cleavage of C-F bond of C6F6 by SIPr in the presence of BF3 led to double C-F activated compound with two tetrafluoro borate counter anions (2), which upon reduction by lithium metal afforded 3. Alternatively, 3 can be directly accessed in one step by reacting SIPr with C6F6 in presence of Mg metal. Compounds 2 and 3 were well characterized spectroscopically and by single-crystal X-ray diffraction studies. Experimental and computational studies support the cumulenic closed-shell singlet state of 3 with a singlet-triplet energy gap (Delta ES-T) of 23.7 kcal mol(-1).
Keywords: C-F activation; Density functional calculations; fluorine; Kekule diradicaloids; saturated NHC

Stepwise nucleophilic substitution to access saturated N-heterocyclic carbene haloboranes with boron-methyl bonds - Kundu, Gargi; Pahar, Sanjukta; Tothadi, Srinu; Sen, Sakya S. (Organometallics, 2020)
Compounds of boranes with N-heterocyclic carbenes are known, yet little attention has been paid to NHC compounds of boron bearing methyl and halogen moieties together. The reason can be attributed to the hazardous methyldichloroborane (MeBCl2), which ignites in air. We describe here convenient solution-phase access to SIDipp.MeBCl2 (SIDipp = 1,3-bis(2,6-diisopropylphenyl)imidazolin-2-ylidene) (3) by a salt metathesis reaction of SIDipp.BCl3 (2) with MeLi. Replacement of the chlorine atoms of 3 with stepwise addition of AgOTf led to the formation of SIDipp.MeBCl(OTf) (4) and SIDipp.MeB(OTf)2 (5). In the case of 4, all of the substituents on the boron atom are different. Subsequently, we extended our synthetic approach to the amidinate system and prepared PhC(NtBu)2B(Me)Cl (7) from the reaction of PhC(NtBu)2BCl2 (6) with MeLi.

Separation of a diastereomeric diol pair using the mechanical properties of crystals - Gamidi, Rama Krishna; Dandawate, Monica; Choudhury, Rahul; Tothadi, Srinu; Nangia, Ashwini; Reddy, D. Srinivasa (Crystengcomm, 2021)
We report the separation of a (2S,3R/S)-3-ethyl-1-phenylhex-5-ene-2,3-diol (ephd) diastereomeric pair with visually indistinguishable acicular morphologies based on their mechanical responses, which is found to be more efficient than conventional separation methods. Furthermore, the molecular crystals of (2S,3R)-ephd show elastic deformation, while (2S,3S)-ephd fractures in a brittle manner under similar conditions.

Structure-property correlation of halogen substituted benzothiazole crystals - Thekkeppat, Nipun P.; Singla, Labhini; Tothadi, Srinu; Das, Priyadip; Choudhury, Angshuman Roy; Ghosh, Soumyajit (Journal of Molecular Structure, 2021)
We have synthesized 3 benzothiazole crystals (1-3) based on existing knowledge of combining flexibility and optical properties towards achieving applications for flexible optoelectronics. However, one crystal was found to be elastically bendable and was found to comply necessary packing features for elasticity. Other two crystals do not obey packing features for elasticity hence they are brittle in nature. Further, Hirshfeld analysis illustrates that elastic crystal 1 possess more number of weak and dispersive interactions compared to other crystals. These interactions were instrumental in invoking elasticity. Moreover, crystals 1-3 were found to be fluorescent as well at specific excitation wavelengths. Therefore, among these crystals, particularly crystal 1 is considered as more promising candidate for flexible optoelectronics. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Benzothiazole crystals; Elasticity; Halogen bond; mechanical properties

Synthesis and application of silylene-stabilized low-coordinate Ag(I)-arene cationic complexes - Parvin, Nasrina; Sen, Nilanjana; Tothadi, Srinu; Muhammed, Shahila; Parameswaran, Pattiyil; Khan, Shabana (Organometallics, 2021)
We report the first examples of N-heterocyclic silylene-stabilized monocoordinate Ag(I) cationic complexes weakly bound to the free arene rings (C6H6, C6Me6, and C7H8). Further, the application of these electrophilic Ag(I) complexes as catalysts has been investigated toward A(3)-coupling reactions, which afforded a series of propargylamines in good to excellent yields with low catalyst loading under a solvent-free condition (19 examples).

Six-membered saturated NHC-stabilized borenium cations: isolation of a cationic analogue of borinic acid - Kundu, Gargi; Balayan, Kajal; Tothadi, Srinu; Sen, Sakya S. (Inorganic Chemistry, 2022)
The reaction of six-membered saturated NHC [1,3-di(2,6-diisopropylphenyl) tetrahydropyrimidine-2-ylidene; henceforth abbreviated as 6-SIDipp] with PhBCl2 yields a Lewis base adduct, 6-SIDipp.PhBCl2 (1), which readily undergoes nucleophilic substitution reaction with AgNO3, leading to the single (2) and double (3) substitution of both chlorides with ONO2 moieties at the boron atom. The reaction of 1 with 1 equiv of AlCl3 resulted in a borenium cation of composition [6-SIDipp.B(Ph)Cl]+ (4) with AlCl4- as the counteranion. Although borenium cations with different substituents on boron have been reported, a structurally characterized phenylchloroborenium cation remains unknown. Similarly, the reaction of 1 with triflic acid provides the first representative of a new class of borenium cations bearing one hydroxyl and one phenyl group on boron (5), a cationic analogue of borinic acid. Ph-BN H Diphenylborinic acid

Substitution at sp(3) boron of a six-membered NHC center dot BH3: convenient access to a dihydroxyborenium cation - Kundu, Gargi; Ajithkumar, V. S.; Raj, K. Vipin; Vanka, Kumar; Tothadi, Srinu; Sen, Sakya S. (Chemical Communications, 2022)
Herein, we have undertaken the synthesis and investigated the reactivity of a 6-membered saturated NHC borane adduct (1). Direct electrophilic halogenation of 1 with a stoichiometric amount of I-2 led to NHC boryl iodides, 6-SIDipp center dot BH2I (2) and 6-SIDipp center dot BHI2 (3), which were further reacted with various nucleophiles to give novel 6-SIDipp based mono and disubstituted boranes with OTf (4 and 6) or ONO2 (5 and 7) functional groups. The addition of Br-2/H2O to 1 smoothly results in a dihydroxyborenium cation (8).

Six-membered NHC stabilized monomeric zinc complexes - Gour, Kritika; Kundu, Gargi; Dash, Soumya Ranjan; Vanka, Kumar; Tothadi, Srinu; Sen, Sakya S. (European Journal of Inorganic Chemistry, 2023)
This paper describes the rare use of a 6-membered saturated N-heterocyclic carbene (NHC) known as 1,3-di(2,6-diisopropylphenyl) tetrahydropyrimidine-2-ylidene (abbreviated as 6-SI-Dipp) as a ligand in zinc chemistry. We report on the investigation of the reactions between 6-SI-Dipp and ZnX2, which resulted in a range of new monomeric 6-SIDipp center dot ZnX2 complexes (X=Et (1), Cl (2), Br (3), and I (4)). We also prepared a new NHC zinc complex where the two substituents of the zinc atom are different, 6-SIDipp center dot Zn(Et)Br (7) through the reaction of the proligand [6-SIDippH]Br with ZnEt2. We have observed that the reactions of complex 1 with sulfur and HBpin led to the removal of the ZnEt2 moiety, resulting in the formation of a C=S double bond and a B H activation product, respectively. Lastly, the reaction of 1 with five-membered NHCs led to the exchange of carbene and the formation of either 5-IDipp center dot ZnEt2 (8) or 5-SIDipp center dot ZnEt2 (9).
Keywords: Lewis adduct; NHC; X-ray diffraction; zinc

Saturated NHC-stabilized borenium, boronium, hydride-bridged boron cations, and a bora-acyl chloride - Kundu, Gargi; Amrutha, P. R.; Tothadi, Srinu; Sen, Sakya S. (ORGANOMETALLICS, 2024)
Keywords: activation; BORINIUM; Chemistry

Synthesis, characterization, and crystal structure of 2-(2-azidophenyl)-3-oxo-3H-indole 1-oxide - Dhote, Pawan; Tothadi, Srinu; Ramana, Chepuri V.; Chopra, D. (Acta Crystallographica Section E Crystallographic Communications, 2024)
<div class="abstract author" id="aep-abstract-id5" style="box-sizing: border-box; margin: 0px 0px 8px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> An attempt to explore the reactivity of the nitro group in the presence of gold catalysis in comparison to the azide group yielded intriguing results. Surprisingly, only the nitro group exhibited reactivity, ultimately giving rise to the formation of the title isatogen. <div class="abstract author" id="aep-abstract-id7" style="box-sizing: border-box; margin: 0px 0px 8px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> An attempt to explore the reactivity of the nitro group in the presence of gold catalysis in comparison to the azide group yielded intriguing results. Surprisingly, only the nitro group exhibited reactivity, ultimately giving rise to the formation of the title isatogen, C14H8N4O2. In the crystal structure, weak C—H⋯O hydrogen bonds and π–π stacking interactions link the molecules. The structure exhibits disorder of the molecule.